An analysis of Antonio Gramsci's theory of "hegemony" in the context of the Indian social system - Santosh Kumar Singh (Knowledgeable Research A Multidisciplinary Journal, 2025)
This paper analyzes Antonio Gramsci's theory of hegemony in the context of the Indian social system. The study aims to understand how structures of dominance are created and operate at the ideological, cultural, and political levels in Indian society. In light of Gramsci's ideas, this research analyzes the mechanisms of dominance inherent in Indian traditions, religious symbols, and the social class system. It also highlights the processes of ideological control and consensus-building through education, media, and politics in modern India.